The Role of Holistic Nurses in Integrative Non-Pharmacological Pain Management - Konthiang, Kattiyaporn; Varee, Acha; Niramon , Poramaporn (Journal of The Royal Thai Army Nurses, 2024)
Pain is an emotional and sensory experience that indicates discomfort due to tissue damage in the body or serves as a warning sign that danger is occurring to the body’s tissues. Effective pain management can respond to pain reduction, which is a role of nurses, taking into account the physical, mental, social, and spiritual aspects. This holistic care can be performed within the professional scope in pain relief activities, combining non-pharmacological methods with medication. By providing care, comfort, and encouragement, patients can feel reassured, which leads to confidence that they will be safe from pain. Pain has a direct impact on daily life, causing discomfort, suffering, and disturbances to mental well-being, as well as affecting the mobility of various parts of the body. Non-pharmacological pain management can integrate holistic care with conventional medicine, incorporating various alternative medicine methods, such as music therapy, meditation, aromatherapy, massage, and herbal remedies. This represents a challenging approach for nurses to manage pain holistically through independent roles. This academic article aims to present the role of holistic nursing in pain management, including the meaning and types of pain, pain assessment, non-pharmacological pain management using an integrative approach, the role of nurses in integrative pain management, and integrated pain management strategies, to provide information for non-pharmacological pain management.